2021
DOI: 10.1038/s41598-021-82572-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma nitriding to improve the wear and corrosion resistance of 18Ni-300 maraging steel manufactured by selective laser melting

Abstract: Abstract18Ni-300 maraging steel manufactured by selective laser melting was plasma nitrided to improve its wear and corrosion resistance. The effects of a prior solution treatment, aging and the combination of both on the microstructure and the properties after nitriding were investigated. The results were compared with conventionally produced 18Ni-300 counterparts subjected to the same heat- and thermo-chemical treatments. The plasma nitriding was performed under the same conditions (temperature of 520 °C and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Nitriding, a process involving surface hardening through nitrogen diffusion under certain temperature conditions, has been known to enhance the mechanical properties of stainless steel, as well as its antibacterial properties, for instance, 316 L stainless steel, 18Ni-300 [6], and 718 alloys martensitic stainless steel, and 718 alloys. Additionally, surface nano crystallization has been observed to have a high chemical activity due to the enhancement of atomic diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Nitriding, a process involving surface hardening through nitrogen diffusion under certain temperature conditions, has been known to enhance the mechanical properties of stainless steel, as well as its antibacterial properties, for instance, 316 L stainless steel, 18Ni-300 [6], and 718 alloys martensitic stainless steel, and 718 alloys. Additionally, surface nano crystallization has been observed to have a high chemical activity due to the enhancement of atomic diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…While aging precipitation treatments improve the mechanical properties of additive-manufactured maraging steels, several authors have also reported that these treatments tend to worsen their corrosion resistance [34,35]. From a practical application standpoint, the poor corrosion resistance of M300 steels compared to other tool steels or stainless steels represents a major challenge for SLM-processed martensitic aged steel parts [36]. As in the mechanical behavior of the material, corrosion resistance in martensitic steels is influenced by both the formation of precipitates and the presence of reversed austenite [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Kurz [18] describes nitriding using nitriding powder and an activator, resulting in a signi cant reduction of nitriding time, achieving similar properties of the nitriding layer as those formed in a salt bath. Several authors present the use of nitriding to improve the properties of primary layers produced by various technologies [19][20][21]. Orečný et al [22] signi cantly increased wear resistance by nitriding high-temperature tempered tool steel.…”
Section: Introductionmentioning
confidence: 99%